Thermal behaviour of polystyrene/silica composites. (4th March 2018) - Alekseeva, Olga V.; Noskov, Andrew V.; Guseynov, Sabir S.; Agafonov, Alexander V.
ABSTRACT: The particle-size distribution in silica powder prepared by the sol–gel method has been determined by dynamic light scattering analysis. The average diameter of the particles was found to be 250 nm. Using a low-temperature nitrogen adsorption–desorption technique, it was found that the synthesised powder may be referred to as mesoporous materials. Polystyrene/silica composite films were fabricated by casting from o-xylene solutions. It was found, using thermogravimetry, that incorporation of silica leads to an increase in both the onset temperature of polymer degradation and in the temperature at which the maximum rate of weight loss occurs. Using differential scanning calorimetry, the phase transitions from the glassy state to the elastic one were studied for the polymeric materials. New data relating to the effect of silica on the glass-transition temperature, T g, of composites with a low weight fraction of SiO2 were found. Specifically, we found a non-monotonic concentration dependence of the value of T g . The present results advocate for employing silica as an effective filler for producing polymer composites with enhanced thermal properties.